EFFECTIVENESS OF BIOCHAR AND MICROBIAL APPLICATIONS IN SWEET SORGUM (SORGUM BICOLOR L.) CROPS ON SEAWATER-INTRUDED MEDIA - Akbar Kurniawan; Rini Sulistiani; Dafni Mawar Tarigan; Wan Arfiani Barus (RADJA PUBLIKA, 2026)
This study aims to determine the effect of biochar and microbial application on the growth and yield of sweet sorgum (Sorghum bicolor L.) in in seawater-intruded media. Biochar functions to improve soil structure and increase water retention and nutrient efficiency, while tobacco microbes have the potential to act as biological agents. The study employed a Split-Plot Design with two factors: biochar (0, 40, 80, 120 g/polybag) and microbes (0, 5, 10, 15 ml/polybag), each with three replications. Analysis results indicated that biochar application significantly influenced the parameters of seeds per panicle and seed weight per plot. The biochar treatment at a dose of 80 g/polybag produced the highest number of seeds per panicle at 74.54 seeds, while the treatment without biochar (B0) yielded the highest seed weight per plot at 57.65 g. The application of microorganisms and the interaction between biochar and microorganisms did not show a significant effect on all observed parameters. Biochar was proven effective in increasing sorghum yield on salt-intruded land through improved generative growth when applied at the optimal dose.